The effect of Chinese herbal medicines on the storage quality of sweet potato - Si, Zengzhi; Men, Fengrui; Liu, Yangyang; Wang, Weicao; Song, Jiale (Frontiers in Plant Science, 2025)
Sweet potato (Ipomoea batatas (L.) Lam.) are prone to damage during harvest and postharvest storage, leading to significant economic value depreciation. To mitigate nutritional degradation and improve storability, the application of appropriate preservatives is essential. Conventional preservation techniques, including physical, chemical, and biological approaches —though effective, present inherent limitations. Recent research has prioritized eco-friendly natural preservatives from Chinese herbal medicines as sustainable alternatives to synthetic biocides. In this study, we evaluated the storability of fourteen sweet potato varieties and assessed the preservation of Chinese herbal extracts on varieties with differential storage tolerance by investigating storage quality. The results showed that the purple-fleshed line JK142 (storage-tolerant representative) exhibited the lowest decay rate and moderate dry matter content; the yellow-fleshed cultivar Jishu 25 (moderately storage-tolerant representative) showed intermediate decay rate but the highest dry matter content; the white-fleshed line JK147 (storage-sensitive representative) displayed the highest decay rate and lowest dry matter content. Consequently, lines JK142 (storage-tolerant), Jishu 25 (moderately tolerant), and JK147 (storage-sensitive) were selected as representatives of three distinct storability levels to systematically evaluate the effects of varying concentrations of five Chinese herbal extracts on sweet potato postharvest preservation. The results revealed that the storage-tolerant cultivar JK142 achieved optimal cost-benefit preservation with 2% Andrographis herba extract; the moderately tolerant Jishu 25 responded best to 0.5% Artemisia argyi extract; the storage-sensitive JK147 required 1% Andrographis herba extract. These results substantiate the theoretical framework for developing plant-derived preservatives and highlight cultivar-specific preservation strategies. The study further establishes a foundation for investigating the mechanistic basis of herbal extract efficacy in postharvest management.